Campylobacter armoricus sp. nov., a novel member of the Campylobacter lari group isolated from surface water and stools from humans with enteric infection. Issue 12 (12th November 2019) - Boukerb, Amine M.; Penny, Christian; Serghine, Joëlle; Walczak, Cécile; Cauchie, Henry-Michel; Miller, William G.; Losch, Serge; Ragimbeau, Catherine; Mossong, Joël; Mégraud, Francis; Lehours, Philippe; Bénéjat, Lucie; et al.
Abstract : During a study on the prevalence and diversity of members of the genus Campylobacte r in a shellfish-harvesting area and its catchment in Brittany, France, six urease-positive isolates of members of the genus Campylobacter were recovered from surface water samples, as well as three isolates from stools of humans displaying enteric infection in the same period. These strains were initially identified as members of the Campylobacter lari group by MALDI-TOF mass spectrometry and placed into a distinct group in the genus Campylobacter, following atpA gene sequence analysis based on whole-genome sequencing data. This taxonomic position was confirmed by phylogenetic analysis of the 16S rRNA, rpoB and hsp60 ( groEL ) loci, and an analysis of the core genome that provided an improved phylogenetic resolution. The average nucleotide identity between the representative strain CA656 T (CCUG 73571 T =CIP 111675 T ) and the type strain of the most closely related species Campylobacter ornithocola WBE38 T was 88.5 %. The strains were found to be microaerobic and anaerobic, motile, non-spore-forming, Gram-stain-negative, spiral-shaped bacteria that exhibit catalase, oxidase and urease activities but not nitrate reduction. This study demonstrates clearly that the nine isolates represent a novel species within the C. lari group, for which the name Campylobacter armoricus is proposed. Here, we present phenotypic and morphological features of the nine strains and the description of their genome sequences. The proposed type strain CA656 T has a 1.589 Mbp chromosome with a DNA G+C content of 28.5 mol% and encodes 1588 predicted coding sequences, 38 tRNAs, and 3 rRNA operons.